Kasaysayan the story of the Filipino people. (Asia Pub., 1998)
Kasaysayan : The Story of the Filipino People is Asia Publishing Company Limitad' special gift to the Filipino nation on the centennial of the declaration of its independence. Kasaysayan should serve well for the research needs of other readers and sholars of Philippine history, which has never been told and presented on this scale." Each volume written by one or more of the country's most authoritative experts in the field- features an index and a list of sources in the end; a general glossary is also provided in Volume Ten, a handy one-volume reference. Timely and engaging essays contributed by many of the country's best writers lend a more personal and often poignant touch to every volume.